Faith on the move toward a theology of migration in Asia - Baggio, Fabio; Brazal, Agnes M. (Quezon City Ateneo De Manila University Press, 2008)
"This is the first work on migration in Asia that deftly blends sociology, anthropology, philosophy, theology, and spirituality to show that migration, now a universal phenomenon, thanks in part to globalization, must be a constant concern of the Church?s mission since it is an expression of the Church?s catholicity and a demand for justice. The essays are uniformly well researched and well written and provide a rich trove of empirical data and theological insights. Faith on the Move is required reading for all Church leaders and those engaged in the ministry with migrants not only in Asia but everywhere."--Prof. Peter C. Phan.
"Out of place", exilic existence in a hyperglobalized world / Victorino A. Cueto -- Japan and Philippines, migration turning points / Felipe L. Muncada -- A critical evaluation of the migrant workers' situation in Taiwan in light of the Catholic social tradition / Lou Aldrich -- Cultural rights of migrants / Agnes M. Brazal -- What are you talking about to each other, as you walk along?" (Lk 24:17), migration in the Bible and our journey of faith / Giovanni Zevola -- The church as "imagined communities" among differentiated social bodies / Emmanuel Serafica de Guzman -- Go-- and make disciples of all nations, migration and mission / William LaRousse -- Migration and Christian hope / Anselm Kyongsuk Min -- Globalizing solidarity through faith encounters in Asia / Anthony Rogers -- Living faith in a strange land / James H. Kroeger.
"The essays in this anthology were first presented as papers in the conference, "Faith on the Move: Toward a Theology of Migration in Asia," July 14-15, 2006, jointly organized by the Scalabrini Migration Center, Episcopal Commission on Migrants and Itinerant People, and the Maryhill School of Theology."
Keywords: Globalization -- Religious aspects -- Christianity; Church work with immigrants -- Asia; Immigrants -- Services for -- Asia; Asians -- Migrations; Asia -- Emigration and immigration -- Religious aspects -- Christianity; Asia -- Emigration and immigration -- Religious aspects -- Catholic Church